Incorporating bazedoxifene/conjugated estrogens into the current paradigm of menopausal therapy - Komm BS; Mirkin S (Dove Medical Press, 2012)
Barry S Komm, Sebastian MirkinPfizer Inc, Collegeville, PA, USAAbstract: Many women experience bothersome vasomotor and vaginal symptoms during the menopausal transition. Decreasing levels of estrogens during menopause are also associated with reduced bone density and an increased risk of osteoporosis. Combined estrogen/progestin therapy (hormone therapy) effectively treats menopausal symptoms and prevents bone loss, but has been associated with some safety and tolerability concerns. A novel menopausal therapy is the tissue selective estrogen complex, which pairs a selective estrogen receptor modulator with one or more estrogens. In preclinical studies, the tissue selective estrogen complex partnering bazedoxifene (BZA) with conjugated estrogens (CE) antagonized stimulation of breast and endometrial tissue, reduced vasomotor instability, and preserved bone mass in rat and mouse models. The specific attributes seen with BZA/CE were different from those observed with other selective estrogen receptor modulator/estrogen pairings. BZA/CE has undergone clinical evaluation in the Phase III Selective estrogens, Menopause, And Response to Therapy (SMART) trials in postmenopausal women with an intact uterus. Of the various doses of BZA/CE evaluated, BZA 20 mg/CE 0.45 mg and 0.625 mg were associated with a low incidence of endometrial hyperplasia (<1%) similar to placebo, and showed significant improvements in hot flushes and vulvar/vaginal symptoms and increases in bone mineral density. BZA 20 mg/CE 0.45 mg and 0.625 mg were associated with a low incidence of breast-related adverse events and demonstrated no difference from placebo in age-related changes in mammographic breast density. Both BZA/CE doses showed a favorable tolerability profile, with no increases in uterine bleeding or breast tenderness, and had positive effects on metabolic parameters and quality of life. BZA/CE may be a promising alternative to hormone therapy for the treatment of menopausal symptoms and prevention of osteoporosis in nonhysterectomized postmenopausal women.Keywords: tissue selective estrogen complex, bazedoxifene, conjugated estrogens, menopause, osteoporosis, vasomotor symptoms